Inovasi Pembelajaran Tari: Higher Order Thinking Skill (HOTS) dan Kearifan Lokal - anggraini, dwi; Hasnawati (Jurnal PGSD, 2023)
This study aims to describe the results of the analysis of SBdP subject matter in the field of dance for high school grades on Higer Order Thinking Skills and material innovation based on local wisdom. The research method used is a literature study with data sources thematic books of teachers and elementary school students SBdP material in the field of high-class Dance in accordance with the 2013 Curriculum. The data collection technique is document analysis with a descriptive method. The results showed that the operational verbs used in learning were dominant at levels C1 to C3, cognitive level C4 appeared 3 times and C6 once. Local wisdom-based learning innovations are very supportive to be applied to Basic Competence in understanding the basics of movement, floor patterns, and regional dance properties. The conclusion of this study is that HOTS-based operational verbs and the development of local wisdom-based materials are needed.